A case report of dacrystic seizures presenting with psychosis (Kerala Journal of Psychiatry, 2020)
Dacrystic seizures present with sudden bursts of crying and often manifest with comorbid psychiatric symptoms. Here, we present the case of a 27-year-old female with an 11-year history of stereotyped patterns of crying spells, associated with fearfulness, suspicions, hallucinatory behaviour, recurrent suicidal gestures and impairment in functioning.  She was treated mostly with antipsychotics, antidepressants and mood stabilizers (for a brief period) irregularly, without adequate improvement. She presented with catatonia, hypokalemia and aspiration pneumonia, following default of medications for one month. With appropriate treatment, her physical condition became stable, when short-lasting bouts of recurrent crying spells were observed, followed by confused behaviour and sleep, along with delusions and hallucinations. Her EEG showed epileptiform discharges; brain imaging was normal. She showed good response to anticonvulsants along with antipsychotics. Such unusual presentations of epilepsy and comorbid psychiatric symptoms warrant a high index of suspicion, for proper diagnosis and management.
Keywords: dacrystic seizures, epileptic crying, psychosis